Associations between MUC1 gene polymorphism and resistance to mastitis, milk production and fertility traits in Murrah water buffaloes* - Rosa, Fernanda Trindade da; Moreira, Carla Giovani Avila; Barbero, Marina Mortati Dias [UNESP]; Lugo, Naudin Alejandro; Camargo, Gregorio Miguel Ferreira de; Borquis, Rusbel Raul; Oliveira, Henrique Nunes de [UNESP]; Boligon, Arione Augusti; Vargas, Lucas de; Moreira, Heden Luiz Marques; Tonhati, Humberto [UNESP]; Souza, Fabio Ricardo Pablos de (Taylor & Francis Ltd, 2020)
MUC1 is a glycoprotein mucin expressed in apical cells of luminal tissues, such as mammary gland luminal cells, which the main function is protect the cell surface from the environment microorganisms. The aim of this study were to identify the polymorphism of MUC1 gene in Murrah breed and to analyze the association between molecular marker and somatic cell counting, milk yield, fat yield, fat percentage, protein yield, protein percentage, age at first calving and calving interval. A total of 179 primiparous Murrah buffaloes were genotyped by PCR technique. Milk-recording were performed periodically to determine fat and protein content and somatic cell count. Three alleles of different lengths were amplified and named allele 1, 2 and 3, respectively. The allele 2 was more frequent followed by allele 3. The MUC1 gene was highly associated with traits related to mastitis resistance and milk percentage. Also was demonstrated a mild association between MUC1 gene and milk protein synthesis and a moderate effect on reproductive trait. The MUC1 gene is polymorphic in water buffaloes of Murrah breed and might be a potential marker to marker-assisted selection for intramammary infection and some milk production traits.
Keywords: Molecular marker; VNTR; dairy buffaloes; mastitis